Filozofia i religia a wychowanie: między świeckimi a religijnymi koncepcjami teleologicznymi - Iwanicki, Juliusz (Biuletyn Historii Wychowania, 2018)
This article is an attempt at analysing educational issues from the perspective of teleology. Teleology is a sub-discipline of philosophical and religious reflection. Providing a purpose is a fundamental act of humans. This type of reflection is also needed in education. The article presents four possible types of relations between philosophy and religion in culture. These various possibilities result in various solutions that can be employed in upbringing. Depending on the adopted system of values, a young person will have a different vision of the world. The article also provides a historical analysis, referring to various classical philosophical and religious systems.